1986
DOI: 10.1152/ajpendo.1986.251.6.e664
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen depletion and increased insulin sensitivity and responsiveness in muscle after exercise

Abstract: As judged by its ability to stimulate glucose uptake and alpha-aminoisobutyric acid (AIB) transport, the sensitivity and the responsiveness of perfused rat muscle to insulin are enhanced after moderately intense treadmill exercise. In fed rats, these enhanced effects of insulin are predominantly restricted to muscles that performed work as evidenced by glycogen depletion. The present study was designed to examine the relationship between glycogen depletion per se and the postexercise changes in insulin action.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 12 publications
5
18
0
Order By: Relevance
“…GLUT4 expression, but not GLUT1, was also increased in muscles with LG. Previous investigations have also reported fasting-induced increases in GLUT4 expression (5) and insulin-stimulated glucose uptake in skeletal muscles (18,44). GLUT4 is expected to transport the majority of glucose into skeletal muscles, and we find it likely that the elevated glucose uptake observed in muscles with LG, at least in part, is a consequence of increased GLUT4 expression.…”
supporting
confidence: 75%
“…GLUT4 expression, but not GLUT1, was also increased in muscles with LG. Previous investigations have also reported fasting-induced increases in GLUT4 expression (5) and insulin-stimulated glucose uptake in skeletal muscles (18,44). GLUT4 is expected to transport the majority of glucose into skeletal muscles, and we find it likely that the elevated glucose uptake observed in muscles with LG, at least in part, is a consequence of increased GLUT4 expression.…”
supporting
confidence: 75%
“…It might have been expected that exercise taken after breakfast would have affected glucose clearance also during the subsequent lunch. However, exerciseinduced enhancement of glucose clearance in the post exercise period is closely related to the depletion of muscle glycogen during exercise [28,29,31], and it wanes as glycogen stores are replenished by food intake [31]. The intensity and duration of exercise applied in the present study would even in the fasting state have been expected to result in only modest muscle glycogen breakdown.…”
Section: Discussionmentioning
confidence: 65%
“…1) (p < 0.05). The mechanism for this may include enhancement of both non-insulin and insulin-mediated glucose transport and disposal [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity is defined as the concentration of insulin required to cause 50% of its maximal effect on glucose uptake, whereas insulin responsiveness is defined as the increase in glucose uptake induced by the maximally effective insulin concentration. Several previous studies reported that an acute bout of exercise enhanced insulin sensitivity in the skeletal muscles of fasted rats within 4 hours after the cessation of exercise, but that it failed to increase insulin responsiveness [7,10,11]. On the other hand, insulin responsiveness was reduced in the muscles of fed rats as compared with fasted rats.…”
Section: Introductionmentioning
confidence: 93%